Ki Hajar Dewantara's thoughts on shaping the character of generation Z towards a golden Indonesia - Yuherman, Yuherman; Yusutria, Yusutria; Taufik, Ahmad; Febriana, Rina (Empathy : Jurnal Fakultas Psikologi, 2024)
The character of Generation Z is facing a significant decline in moral values, presenting the impression of being increasingly unruly. As the next generation responsible for advancing the nation toward a Golden Indonesia, this degradation affects various aspects, including speech, behavior, lifestyle, and education. Character education is currently in decline due to the dominance of media and the rapid progress of science and technology. The challenges facing Generation Z, characterized by the aspiration for a Golden Indonesia, demand a thoughtful approach to address these issues an approach found in the ideas of Ki Hajar Dewantara. This study aims to explore Ki Hajar Dewantara’s thoughts on shaping the character of Generation Z in alignment with the vision of a Golden Indonesia. The research adopts a literature review methodology, gathering data from various sources. The data collection technique involves documentation, specifically collecting relevant library resources. The study is conducted systematically, processing and synthesizing the data to provide conclusions based on the literature. The findings reveal that Ki Hajar Dewantara’s ideas focus on character development through the consideration of educational patterns, teacher and student roles, and methods for instilling character education values in future leaders aligned with the vision of a Golden Indonesia.